2020
DOI: 10.1111/obr.13128
|View full text |Cite|
|
Sign up to set email alerts
|

Individuals with obesity and COVID‐19: A global perspective on the epidemiology and biological relationships

Abstract: Summary The linkage of individuals with obesity and COVID‐19 is controversial and lacks systematic reviews. After a systematic search of the Chinese and English language literature on COVID‐19, 75 studies were used to conduct a series of meta‐analyses on the relationship of individuals with obesity–COVID‐19 over the full spectrum from risk to mortality. A systematic review of the mechanistic pathways for COVID‐19 and individuals with obesity is presented. Pooled analysis show individuals with obesity were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

43
900
16
55

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 987 publications
(1,014 citation statements)
references
References 221 publications
43
900
16
55
Order By: Relevance
“…14 comorbid conditions during triage may allow for risk stratification and identification of patients who may benefit from increased monitoring and interventions. 14,15 We examined the CDC listed risk factors as a starting point. These risk factors were largely consistent with those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…14 comorbid conditions during triage may allow for risk stratification and identification of patients who may benefit from increased monitoring and interventions. 14,15 We examined the CDC listed risk factors as a starting point. These risk factors were largely consistent with those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Even after adjusting for age and obesity-related comorbidities such as diabetes, hypertension and coronary heart disease, obesity remains a strong independent predictor of excess morbidity and mortality. 1,4,5 These findings although concerning are not entirely unexpected. 6 Obesity and poor clinical outcomes have been described with other viral pathogens, most notably influenza A (H1N1) during the 2009 pandemic, when obesity was associated with increased hospitalizations, need for intensive care support, and deaths.…”
Section: Introductionmentioning
confidence: 70%
“…6 Obesity and poor clinical outcomes have been described with other viral pathogens, most notably influenza A (H1N1) during the 2009 pandemic, when obesity was associated with increased hospitalizations, need for intensive care support, and deaths. 4,7,8 In addition to the relationship between obesity and clinical outcomes, emerging evidence suggests a link between higher body mass index (BMI) and higher incidence rates of COVID-19 or SARS-CoV-2 infection 4,9,10 suggesting increased BMI may enhance susceptibility to infection. If correct, there would be important implications for individual-level risks and population-level transmission dynamics, particularly among populations with high rates of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…ARDS Subject Demographics.There is ongoing research to evaluate the implications of obesity within the context of COVID-19. A systematic review by Yang, et al[21] identifi ed a greater severity of COVID-19 in patients with higher BMI, and a recent systematic review by Popkin, et al[22] revealed that obesity placed patients at higher risk for development of COVID-19 with increased hospitalization, ICU admission, and overall mortality. As the COVID-19 pandemic persists, ARDS and COVID-19 induced respiratory failure may be diffi cult to diff erentiate and the clinical management strategies for each variable[23].…”
mentioning
confidence: 99%